2008
DOI: 10.1016/j.jstrokecerebrovasdis.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

LOAD: A Pilot Study of the Safety of Loading of Aspirin and Clopidogrel in Acute Ischemic Stroke and Transient Ischemic Attack

Abstract: Background: Most patients with ischemic stroke present to the emergency department beyond the approved 3-hour time window for thrombolytic or other revascularization therapies. Clopidogrel and aspirin loading is commonly used to prevent deterioration in other acute vascular occlusive events. This pilot study examined the safety of antiplatelet loading in acute ischemic stroke and transient ischemic attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…Examination of 40 acute ischemic stroke patients with a mean initial NIHSS score of 6 found the incidence of progressive stroke was 0% with the combination of aspirin and clopidogrel, if neurological deterioration was defined as an increase of 2 points or more on NIHSS, but symptomatic intracranial hemorrhage occurred at 43 hours posttreatment in one patient. 17) The present protocol of low-dose aspirin and cilostazol for acute ischemic stroke had a tolerable …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Examination of 40 acute ischemic stroke patients with a mean initial NIHSS score of 6 found the incidence of progressive stroke was 0% with the combination of aspirin and clopidogrel, if neurological deterioration was defined as an increase of 2 points or more on NIHSS, but symptomatic intracranial hemorrhage occurred at 43 hours posttreatment in one patient. 17) The present protocol of low-dose aspirin and cilostazol for acute ischemic stroke had a tolerable …”
Section: Discussionmentioning
confidence: 81%
“…2,4,8,9,13,14,17,20,22,27,30) Patients with progressive stroke have worse neurological scores on the initial NIHSS, and the greatest likelihood of predicting progression occurs with stratification by initial NIHSS scores of 7 or less and more than 7. 9,30) Therefore, the low incidence of progressive stroke in this study may be tied to the tendency to enroll mild cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 The combination of aspirin and clopidogrel in patients with mild deficits was associated with a lower risk of neurologic deterioration compared with matched controls (OR 17.2, p 5 0.002). 46 In those patients, mechanisms such as a substenotic ulcerated plaque in the main vessel may be the cause. Indirect evidence for a more aggressive antithrombotic approach among patients with small vessel disease also comes from the original National Institute of Neurological Disorders and Stroke trial of IV tissue plasminogen activator in acute ischemic stroke, which demonstrated an even greater benefit for tissue plasminogen activator treatment among patients with small vessel stroke (25% absolute risk reduction of a poor outcome on the Barthel Index) than among patients with other stroke subtypes.…”
Section: Noacs In Patients With Intracranial Atherosclerosismentioning
confidence: 99%
“…1 Human studies have shown improved stroke outcome with acute antiplatelet loading, with no significant risk of hemorrhage. [2][3][4] The purpose of this proofof-concept study was to evaluate dose-related efficacy of acute antiplatelet loading on stroke outcome by comparing the following: (1) standard treatment of aspirin (ASA; 5 mg/kg), (2) usual dose dual antiplatelet loading (UD; ASA 10 mg/kg+10 mg/kg clopidogrel), and (3) high-dose dual antiplatelet loading (HD; ASA 10 mg/kg+30 mg/kg clopidogrel). Coprimary end points were (1) platelet inhibition and (2) behavioral outcome as measured by the P 50 (milligrams of clot that leads to neurological dysfunction in 50% of animals in a group) 24 hours after stroke in the rabbit small clot embolic stroke model.…”
mentioning
confidence: 99%